Fintech innovations and Islamic banking performance: Post-pandemic challenges and opportunities - Abdul Aziz Abdul Rahman; Habeeb Ur Rahiman; Abdelrhman Meero; Ahmed Rashad Amin (Banks and Bank Systems, 2023)
This study explores the pivotal role of financial technology (FinTech) in the performance of Islamic banks and financial institutions, considering both challenges and opportunities encountered during the pandemic-induced market disruptions. Amid lockdowns and economic uncertainties, the study delves into the strategies adopted by several countries, with a particular emphasis on Gulf Cooperation Council (GCC) countries, along with Jordan, Indonesia, Malaysia, and Pakistan, underscoring the importance of technological innovation in fostering a dynamic Islamic finance sector. Utilizing a data analysis approach, the study assesses the impact of heightened digitalization and the integration of FinTech on the resilience of the Islamic finance industry within an inherently volatile environment, marked by challenges during pre and post pandemics. The findings reveal that the adoption of FinTech fortifies the industry’s resilience and unveils novel growth prospects. However, the study also identifies potential avenues for expansion, particularly in Sukuk issuance, through the implementation of regulatory guidelines and faster adoption. The research underscores the transformative influence of financial technology reforms on the growth trajectory of Islamic banks. In light of the superior performance of Islamic banking in selected domains, this study advocates for a paradigm shift within the industry, encouraging the robust development of FinTech solutions to enhance its global market presence. AcknowledgmentThe authors would like to acknowledge that this research work was partially financed by Kingdom University, Bahrain from the research grant number: 2023 - 10 - 012.